[OP.4B.06] FREQUENCY OF PRIMARY ALDOSTERONISM IN PATIENTS WITH OBSTRUCTIVE SLEEP APNEA – OSA-PA STUDY. (September 2017) - Karcz, M.; Obarska, J.; Bobrowski, R.; Lewko, D.; Drab, M.; Kolodziejczyk-kruk, S.; Warchol-Celinska, E.; Pregowska-Chwala, B.; Janas, J.; Janaszek-Sitkowska, H.; Kabat, M.; Ambroziak, U.; et al.
Abstract : Objective: The pathophysiological overlap between primary aldosteronism (PA) and obstructive sleep apnea (OSA) has been suggested. Therefore in a prospective OSA-PA study we have evaluated the frequency of PA in patients suspected of OSA. Design and method: We included in our ongoing study 200 consecutive hypertensive patients (mean age 53.2 ± 13.2 years, 127 M, 63 F) referred for polysomnography (PSG) on the basis of one or more of the following clinical features suggestive for OSA: typical symptoms, resistant or difficult-to-treat HT and comorbidities known to be associated with OSA and high cardiovascular risk. Clinically important moderate-to-severe OSA was diagnosed if the apnea/hypopnea index (AHI) was > 15 events/h. PA was diagnosed if the salt infusion test (SIT) was abnormal (postinfusion plasma aldosterone levels >10 ng/dl). Age, gender, office blood pressure levels, sodium, glucose, potassium and creatinine plasma concentrations, presence of metabolic syndrome (MS) and its components (abdominal obesity, glucose metabolism alterations [increased fasting glucose or diabetes], increased triglycerides, decreased HDL cholesterol levels), known cardiovascular disease (CVD) were recorded. Results: OSA was diagnosed in 91 patients (45.5% of the whole group). PA was diagnosed in 19 patients with OSA (20.9%) as compared to 8 patients in the group without OSA (7.3%; p = 0.005). The prevalence of PA was higher in patients with severe than with moderate OSA (16.7% and 24.5%; p = 0.011). Patients with OSA and PA tended to be more males than patients with OSA and without PA (89.5% vs 68.1%; p = 0.052). There were no significant differences between patients with OSA and PA as compared with patients with OSA without PA in regard to age, BMI, blood pressure levels, glucose, creatinine and potassium concentrations as well in the frequency of MS and its components, CVD. Patients with OSA and PA as compared to patients with OSA without PA were characterized by higher sodium concentration (142.9 ± 2.2 vs 141.4 ± 2.2; p = 0.015). Conclusions: Our data indicated that patients with clinically important moderate-to-severe OSA are characterized by relatively high frequency of PA. Our result support the recommendations to screen OSA patients for PA.